ORGANIZATIONAL STRUCTURE ASPECT FOR THE IMPROVEMENT OF PRODUCTIVITY. CASE OF DAIRY MICRO ENTERPRISES IN CEBADAS.. - Ruilova Avila, Carla Belén; Chafla Granda, Jorge JLuis; Esparza Paz, Franqui Fernando; Sánchez Chávez, Roberto Fabián (mktDESCUBRE; Vol 1 No 2 (2020): Special Edition 3rd International Scientific Congress of Administrative and Financial Sciences FADE 2019, 2020)
The analysis of the organizational structure of microenterprises helps determine the interrelationship between the production and management part; It is also the first reference to understand the organization and its relationship. Not having an adequate organizational structure creates confusion in management and functions, production delays and a reduced business vision. The research analyzes the organizational structure and the formation of the dairy production units of the Cebadas parish, as well as the set of endogenous and exogenous factors that affect microenterprise management and productivity. The present study is the result of applied research techniques such as direct observation, interviews, and questionnaires to productive actors. The scope of the research is to improve the opportunity cost in the use of available resources, generate guidelines to improve productivity based on having a clear business organization whose final result is to achieve compliance with organizational goals and objectives and finally Suggest a management model that allows them to perform optimal management based on the quality standards of dairy products with a national focus.